2007
DOI: 10.1562/0031-8655(2001)0730685pmcams2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically Modified α-Crystallin: A Model System for Aging in the Primate Lens¶

Abstract: The purpose of this study was to quantitatively study the changes that occur upon irradiation of 3-hydroxykynurenine (3-HK) in the presence of ␣-crystallin under conditions similar to those in the lens. The samples were prepared in 10 mM phosphate buffer at pH 7.4, bubbled with O 2 or Ar and irradiated with 300-400 nm light. The amount of light absorbed by the samples (I abs ) was measured using azobenzene as an actinometer. Modifications to ␣-crystallin were monitored by ultraviolet-visible and fluorescence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Thus, its fluorescence contribution would be negligible even if 3‐OH‐kynurenine contributes to the yellow hue of the human lens. It would be of interest to compare argpyrimidine and pentosidine to various derivatives of kynurenine to lens proteins, which are believed to be much more fluorescent than kynurenine itself (12,17,25). However, to our knowledge, those compounds are not commercially available.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, its fluorescence contribution would be negligible even if 3‐OH‐kynurenine contributes to the yellow hue of the human lens. It would be of interest to compare argpyrimidine and pentosidine to various derivatives of kynurenine to lens proteins, which are believed to be much more fluorescent than kynurenine itself (12,17,25). However, to our knowledge, those compounds are not commercially available.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this study was to monitor the accumulation of lipofuscin in murine eyes, to compare these spectra with those from eyes from other species, and to compare these data with other tissues. Previous attempts to characterize age‐related changes in eyes were based on absorption study of primate lens (34,35) and transmission of light to the human retina (36). Roberts et al .…”
Section: Introductionmentioning
confidence: 99%
“…In α-crystallin, tryptophans are not located at the N terminus and hence do not have a free amino group to participate in the Maillard reaction. Dillon et al have studied extensively on the photo-degradation products of alpha crystallin and showed that they were primarily from tryptophan oxidation (Dillon 1991;Ervin et al 2001;Finley et al 1997Finley et al , 1998Gaillard et al 2000;McDermott et al 1991;Roberts et al 1991).…”
Section: Resultsmentioning
confidence: 99%